(untitled) (Anclajes, 2024)
The circulation of strategies that aim to dismantle the effects of patriarchy in language has given rise to discussions around the legitimacy of non-sexist uses of language, awakening the interest of different social actors including language institutions such as the Royal Spanish Academy and the Chilean Academy of Language. From the glottopolitical perspective, the objective of this study is to analyze the linguistic ideologies that underlie the interventions that form part of a cycle of conferences organized by the Chilean Academy of Language. The corpus was analyzed under the theoretical and methodological guidelines of the French school of Discourse Analysis. The results show that the linguistic ideologies underlying the interventions are anchored on a heteronormative and patriarchal ideological system, in which the Chilean Academy of Language seeks to legitimize itself: on the one hand, through the construction of a progressive self-image, and, on the other, from their role as experts.